Preparation of alcohol-phase conductive polymer by solvent exchange, method and application
Through solvent exchange and post-treatment technology, the dispersion and conductivity of PEDOT in alcohol are improved, and the lack of high-work function anodes in optoelectronic devices is solved, and the efficient preparation and wide application of alcohol-phase conductive polymer electrodes are achieved.
Patent Information
- Application Number
- CN202310183746.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-02-28
AI Technical Summary
At present, high-work function anodes prepared by solution in optoelectronic devices are lacking, and the traditional commercial PEDOT is difficult to form films on the hydrophobic surface of anionic aqueous solution, and its work function is low, making it difficult to meet the needs of large-scale production and application.
By filling the aqueous PEDOT:pair anion solution into a semipermeable membrane and soaking it in alcohol, solvent exchange is achieved using the selective permeability of the semipermeable membrane, and introducing the second and more pair anions through post-treatment, thereby improving the dispersion and conductivity of PEDOT in different solvents.
The prepared alcohol-phase conductive polymer electrode has good wetting properties without the need for additional anode interface modification layer. The conductivity and work function are adjustable. It is suitable for various optoelectronic devices, solving the lack of high work function electrodes.
Smart Images

Figure CN116239803B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optoelectronic materials, and more specifically, relates to a method and application of preparing alcohol-phase conductive polymers by solvent exchange. Background Art
[0002] In recent years, with the rapid development of optoelectronic information technology, optoelectronic devices have gradually become a research hotspot. In optoelectronic devices, the most commonly used top electrode is a thermally evaporated metal electrode (gold, silver, aluminum, etc.). The metal electrode needs to be thermally deposited under vacuum conditions, which has high requirements on equipment and is difficult to achieve large-scale production. In order to achieve large-scale printing production of optoelectronic devices, the development of solution-processable electrodes has become a hot topic of concern. High-performance solution-processable electrodes must have the properties of high conductivity, low surface energy and adjustable work function. At present, common solution-processable electrode materials include: metal nanowires (gold, silver, etc.), liquid metals (indium gallium alloys, etc.) and conductive polymers. Among them, metal nanowires have good optoelectronic properties, but the film roughness is high, which is not conducive to the preparation of subsequent device functional layers. Liquid metals have high conductivity, but it is difficult to infiltrate the surface of organic films.
[0003] Conductive polymer poly(3,4-ethylenedioxythiophene) (PEDOT) has high conductivity. By introducing anions such as polystyrene sulfonic acid (PSS) and perfluorosulfonic acid polymer (PFSA) during the synthesis process, it can be dispersed in the solution and can be processed in solution. PEDOT: anion aqueous solution has the characteristics of work function, adjustable transmittance and small surface roughness, and can be widely used in the fields of photoelectric device collection and injection of carriers, antistatic coatings, thermoelectric materials, etc. The PEDOT: PSS aqueous solution developed by Heraeus of Germany and Agfa of Belgium has been successfully commercialized. However, the surface energy of PEDOT: PSS aqueous dispersion is high, and it is difficult to form a film on the hydrophobic film surface. In addition, the work function of PEDOT: PSS is low. When the PEDOT: PSS electrode is used as an anode, an interface material is often required to modify the electrode. At present, there is a lack of one-piece printable electrodes with good wettability and high work function. It is urgent to develop a preparation formula for one-piece alcohol phase electrodes with simple process suitable for commercial large-scale production.
[0004] In the invention patent with the publication number CN114316223A, a new type of conductive polyethylene dioxythiophene alcohol dispersion using perfluorosulfonic acid polymer as anion is disclosed, which can be applied to the hole transport layer of solar cells, light-emitting diodes, antistatic coatings, electrochromic, thermoelectric materials and bioelectronics. The selection of anions in this patent is limited to one perfluorosulfonic acid polymer. Since its solubility in ethanol is better than its solubility in other solvents, when preparing other solvents such as butanol and dimethyl sulfoxide as PEDOT dispersions, perfluorosulfonic acid polymer (PFSA) anions are not the best choice. In the present invention, a PEDOT: anion solution can be selected before dialysis exchange, and a second and more anions can be introduced through post-treatment after dialysis exchange to improve the dispersibility of PEDOT in different solvents, and the post-treatment can also modify its conductivity and work function. Summary of the invention
[0005] In view of the deficiencies of the prior art and the need for improvement, the present invention provides a method for preparing an alcohol-phase conductive polymer by solvent exchange, wherein an aqueous PEDOT: anion solution is loaded into a semipermeable membrane and immersed in alcohol, and the selective permeability of the semipermeable membrane is utilized to achieve solvent exchange, and a PEDOT alcohol solution with a high conductivity and adjustable work function is obtained by post-treatment (adding other anions and alcohol). The electrode prepared by the alcohol-phase conductive polymer has good wettability on various interfaces, does not need to add an additional anode interface modification layer, and can be well applied to various optoelectronic devices, thereby solving the problem of the lack of high work function electrodes that can be prepared by solution in optoelectronic devices at this stage.
[0006] According to a first aspect of the present invention, there is provided a method for preparing an alcohol phase conductive polymer by solvent exchange, comprising the following steps:
[0007] (1) placing polyethylene dioxythiophene and an aqueous solution of a counter anion into a semipermeable membrane bag, and immersing the semipermeable membrane bag in a first alcohol solvent; due to the difference in polarity between the water solvent and the first alcohol solvent, the water solvent seeps out of the semipermeable membrane bag, while the first alcohol solvent permeates into the semipermeable membrane bag, thereby achieving solvent exchange;
[0008] (2) Adding a second alcohol solvent into the semipermeable membrane bag to uniformly disperse the polyethylenedioxythiophene to obtain the alcohol-phase conductive polymer.
[0009] Preferably, the counter anion is at least one of polystyrene sulfonic acid, high fluoride sulfonic acid ionomer, sulfonated polyamic acid, sodium alkylbenzene sulfonate, fatty alcohol sulfate and sodium polystyrene sulfonate.
[0010] Preferably, in step (2), after adding the second alcohol solvent, the step further includes adding other types of counter anions not present in the semipermeable membrane bag.
[0011] Preferably, in the aqueous solution, the molar ratio of polyethylenedioxythiophene to the anion substance is 1:(2.5-30).
[0012] Preferably, the first alcohol solvent described in step (1) and the second alcohol solvent described in step (2) are each independently selected from C1-C10 aliphatic alcohols, alicyclic alcohols or aromatic alcohols.
[0013] According to another aspect of the present invention, an alcohol-phase conductive polymer prepared by any one of the methods is provided.
[0014] According to another aspect of the present invention, there is provided a use of the alcohol-phase conductive polymer for preparing a thin film.
[0015] According to another aspect of the present invention, a film obtained by the application is provided.
[0016] Preferably, the conductivity of the film is 10 -4 -10 3 S cm -1 , the work function is 4.1-5.4eV.
[0017] According to another aspect of the present invention, there is provided an application of the film, specifically an application in a solar cell electrode, a solar cell hole transport layer, an antistatic film, a thermoelectric device or a light emitting diode.
[0018] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0019] (1) The present invention places a conductive polyethylene dioxythiophene aqueous dispersion (PEDOT: counter anion) aqueous solution into a semipermeable membrane and soaks it in an alcohol solvent for penetration. Due to the difference in polarity between the aqueous solvent and the alcohol solvent, different solvents pass through the semipermeable membrane at different speeds, thereby achieving solvent exchange of PEDOT: counter anion. In addition, by introducing two or more counter anions, the work function of the PEDOT: counter anion alcohol solution can be adjusted, thereby achieving a PEDOT: counter anion alcohol dispersion with high work function and high conductivity. The electrode prepared with this alcohol-phase conductive polymer has good wettability on various interfaces, does not require an additional anode interface modification layer, and can be well applied to various optoelectronic devices, thereby solving the problem of the lack of high work function anodes that can be prepared by solution in current optoelectronic devices.
[0020] (2) The obtained alcohol phase PEDOT electrode has good wettability and adjustable work function (4.1-5.4 eV). The conductivity range of the film prepared by the alcohol phase conductive polymer is 10 -4 -10 3 S cm -1The alcohol phase conductive polymer of the present invention is suitable for organic solar cells with different structures, and the alcohol phase conductive polymer can be effectively used as a device anode without introducing an additional anode interface modification layer. Other application fields of the alcohol phase conductive polymer prepared by the present invention include antistatic coatings, light emitting diodes, thermoelectric materials, etc.
[0021] (3) The solvent exchange strategy provided by the present invention to prepare the alcohol phase conductive polymer formula overcomes the problem of traditional commercial PEDOT: the anion aqueous solution does not wet when coated on a hydrophobic surface. The alcohol dispersion has a small surface tension and can be coated on any surface to prepare a uniform conductive film.
[0022] (4) The solvent exchange strategy provided by the present invention is simple in process. Solvent exchange can be achieved by directly permeating the aqueous phase PEDOT to the anion to obtain conductive solutions of various solvents. The preparation process is independent of large-scale equipment and vacuum degree.
[0023] (5) The solvent exchange strategy provided by the present invention is used to prepare alcohol-phase conductive polymers. The permeation rate can be controlled by controlling the permeation time and the volume of the solvent to be exchanged to achieve regulation of the alcohol content in the conductive solution formula.
[0024] (6) Due to the addition of different pairs of anions, a high-dipole covalent bond is introduced. When the solution forms a film, a dipole is formed on the film surface, which increases the work function of the PEDOT: anion dispersion. In the preparation of solar cells, a higher work function is conducive to the formation of an upward band bending and ohmic contact at the interface between the electrode and the organic semiconductor active layer, thereby achieving efficient hole collection.
[0025] (7) The solvent exchange strategy provided by the present invention is used to prepare an alcohol-phase conductive polymer formula with adjustable work function and conductivity, which is suitable for different types of solar cells, antistatic films, thermoelectric devices, light-emitting diodes and bioelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The invention discloses a process for preparing alcohol-phase conductive polymer by using a solvent exchange strategy.
[0027] Figure 2 (a) is the transmittance diagram of the alcohol phase polymer PEDOT:PSS electrode (e-PH1000) film. Figure 2 (b) Work function test diagram of the film prepared from alcohol phase polymer PEDOT:PSS solution.
[0028] Figure 3 This is the conductivity test graph of the alcohol phase polymer PEDOT:PSS electrode (e-PH1000) film.
[0029] Figure 4 (a) Schematic diagram of the inverse structure organic solar cell of the present invention (e-PH1000 as anode), Figure 4 (b) Current density-voltage (JV) curve of the corresponding device structure.
[0030] Figure 5 (a) Schematic diagram of the inverse structure organic solar cell of the present invention (e-4083 as a hole transport layer), Figure 5 (b) Current density-voltage (JV) curve of the corresponding device structure.
[0031] Figure 6 Temperature difference-voltage curve of a thermoelectric device. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0033] Figure 1 The present invention is a process for preparing alcohol phase conductive polymer by solvent exchange strategy. The present invention is a method for preparing alcohol phase conductive polymer by solvent exchange, comprising the following steps:
[0034] (1) polyethylene dioxythiophene and an aqueous solution of anions are placed in a semipermeable membrane bag, and the semipermeable membrane bag is immersed in an alcohol solvent. Due to the difference in polarity between the water solvent and the alcohol solvent, the water solvent seeps out of the semipermeable membrane bag, while the alcohol solvent permeates into the semipermeable membrane bag, thereby achieving solvent exchange;
[0035] (2) adding alcohol into the semipermeable membrane bag, wherein the alcohol is the same as or different from the alcohol solvent in step (1), so that the polyethylenedioxythiophene is evenly dispersed, thereby obtaining the alcohol phase conductive polymer.
[0036] In some embodiments, the counter anion is at least one of polystyrene sulfonic acid (PSS), perfluorinated sulfonic acid ionomer (PFSA), sulfonated polyamic acid (SPAA), sodium alkylbenzene sulfonate (LAS), fatty alcohol sulfate (FAS) and sodium polystyrene sulfonate (PSSNa).
[0037] In some embodiments, the semipermeable membrane is a dialysis membrane made of regenerated cellulose, cellulose resin, or PVDF, and the MWCO of the retained molecule ranges from 100 to 50,000 Da.
[0038] In some embodiments, the alcohol content can be achieved by controlling the permeation treatment time and the additional addition of alcohol, and the final alcohol concentration is 5%-99%.
[0039] In some embodiments, the commercial products PEDOT:PSS aqueous solutions selected include HSolar, PH500, 4083, PH1000, CH8000 and the like.
[0040] In some embodiments, the conductivity of the film prepared by the alcohol phase conductive polymer formula is 10 -4 -10 3 Scm -1 It is internally adjustable, and the work function is adjustable within 4.1-5.4eV. It can be prepared into films by spin coating, scraping, spraying and other processes. It can be used to prepare solar cell electrodes, solar cell hole transport layers, antistatic films, thermoelectric devices, light-emitting diodes, etc.
[0041] In some embodiments, compared with alcohol phase PEDOT:PSS solutions prepared by other methods, such as removing water from commercial PH1000 by ultrafiltration and adding ethanol as a dispersion liquid, a conductive PEDOT:PSS ethanol dispersion is prepared [NPG Asia Mater 12,65 (2020)]. Since the dispersion concentration of the anion PSS in alcohol in this formula is low (less than 5 mg / mL), it is difficult to obtain a stable PEDOT:PSS alcohol dispersion using PSS as the anion. The performance of organic solar cells proves that it is less suitable for use as an anode in organic solar cells than the present invention.
[0042] Example 1
[0043] The process of preparing alcohol-phase conductive polymer by solvent exchange strategy described in the present invention is as follows: 6 mL of aqueous PEDOT:PSS (PH1000) with a mass ratio of 1:2.5 is loaded into a cellulose lipid semipermeable membrane with a molecular weight cutoff of 500 Da, and soaked in 500 mL of ethanol. The polarities of ethanol and water are 0.654 and 1.000, respectively, and the speed of water molecules with high polarity passing through the semipermeable membrane is faster than that of ethanol molecules. After 35 minutes of penetration, 90% of water molecules penetrate into the ethanol solution from the dialysis bag, and then 6 mL of ethanol and 5 wt% of ethylene glycol secondary dopant are added to PEDOT:PSS, and a cavitation effect is generated in the liquid by strong ultrasound. The solid particles in the liquid are completely dispersed by an ultrasonic cell crusher for 2 hours to obtain an ethanol-phase polymer PEDOT:PSS solution (e-PH1000).
[0044] The film was processed by spin coating, and the alcohol phase PEDOT:PSS solution was dynamically spin coated on clean glass at a spin coating speed of 800 rpm. After spin coating, the film was annealed at 100°C for 3 minutes to wait for the alcohol solvent to evaporate. The obtained film thickness was 160nm, and its square resistance was 100Ω / sq. Taking the alcohol phase PEDOT:PSS film with a thickness of 160nm as an example, its transmittance curve is as follows Figure 2 As shown in (a), the work function test is 4.9eV. Figure 2 As shown in (b) in .
[0045] Example 2
[0046] The process of preparing alcohol-phase conductive polymer by solvent exchange strategy described in the present invention can be applied to other polar alcohol solvents. The commonly used polar solvents are shown in Table 1. Taking n-butanol as an example, the solvent exchange is implemented to prepare n-butanol phase PEDOT:PSS solution: 3mL of aqueous phase PEDOT:PSS (PH1000) is loaded into a cellulose lipid semipermeable membrane with a molecular weight cutoff of 500Da, and it is soaked in 300mL of n-butanol solution. The polarity of n-butanol and water is 0.586 and 1.000 respectively. The speed of water molecules with high polarity passing through the semipermeable membrane is faster than that of n-butanol molecules. Infiltrate for 15mins until 95% of water molecules penetrate into n-butanol from the dialysis bag, then add 3mL of n-butanol to PEDOT:PSS, and use an ultrasonic cell crusher to treat for 2h to completely disperse the solid particles in the liquid in the n-butanol solvent to obtain a n-butanol phase polymer PEDOT:PSS solution.
[0047] The film was processed by spin coating, and the prepared n-butanol phase PEDOT:PSS solution was dynamically spin-coated on clean glass at a spin coating speed of 800 rpm. After spin coating, it was annealed at 100°C for 3 minutes to wait for the alcohol solvent to evaporate, and the obtained film thickness was 170nm.
[0048] Table 1 Polarity of alcohol solvents
[0049]
[0050] Example 3
[0051] The process of preparing alcohol-phase conductive polymer by solvent exchange strategy described in the present invention can be applied to other types of semipermeable membranes, wherein the types of semipermeable membranes are dialysis membranes made of regenerated cellulose, cellulose resin, and polyvinylidene fluoride (PVDF), and the molecular weight cutoff ranges from 100 to 50000Da. Below, taking a cellulose resin semipermeable membrane with a molecular weight cutoff of 3000Da as an example, solvent exchange is implemented to prepare an ethanol phase PEDOT:PSS solution: 6mL of aqueous phase PEDOT:PSS (PH1000) with a mass ratio of 1:2.5 is loaded into a cellulose resin semipermeable membrane with a molecular weight cutoff of 3000Da, and it is soaked in 500mL of ethanol solution. Infiltrate for 25mins until 88% of the water molecules penetrate into ethanol from the dialysis bag, then add 6mL of ethanol to PEDOT:PSS, and use an ultrasonic cell crusher to treat for 2h to completely disperse the solid particles in the liquid in the ethanol solution to obtain an ethanol phase polymer PEDOT:PSS solution.
[0052] The film was processed by spin coating, and the prepared alcohol phase PEDOT:PSS solution was dynamically spin coated on clean glass at a spin coating speed of 800 rpm. After the spin coating was completed, it was annealed at 100°C for 3 minutes to wait for the alcohol solvent to evaporate, and the obtained film thickness was 180nm.
[0053] Example 4
[0054] The solvent exchange strategy described in the present invention is used to prepare the alcohol phase conductive polymer formula: 4 mg / mL of high fluorinated sulfonic acid ion polymer (PFSA) is added to 6 mL of the alcohol phase PEDOT:PSS (e-PH1000) solution prepared in Example 1 as the anion and stirred for 1 hour. The film is processed by spin coating, and the prepared PEDOT:PSS solution is dynamically spin coated on clean glass at a spin coating speed of 800 rpm. After the spin coating is completed, annealing is performed at 100°C for 3 minutes to wait for the alcohol solvent to evaporate, and the obtained film thickness is 150 nm. Its work function is tested to be 5.4 eV, which is higher than the original work function of the aqueous phase PEDOT:PSS (PH1000) film of 4.9 eV. The conductivity of the alcohol phase conductive polymer of this formula is tested to be 5.3×10 2 S / cm. The conductivity of the 150 nm film was calculated and the conductivity test was as follows: Figure 3 shown.
[0055] Example 5
[0056] The solvent exchange strategy of the present invention is used to prepare an alcohol-phase conductive polymer formula to prepare an organic solar cell with a trans-structure, which does not require a hole transport layer and can be directly used as an anode.
[0057] (1) Solvent exchange strategy for preparing alcohol phase conductive polymer formulation: Example 4 was repeated with the same steps as described.
[0058] (2) Preparation of inverse organic solar cells: The device structure of inverse organic solar cells is as follows Figure 4 As shown in (a), it is glass / ITO / PEI-Zn / PM6:BTP-eC9:PC 71 BM / e-PH1000. Among them, ITO glass is the bottom electrode, PEI-Zn is the electron transport layer, PM6:BTP-eC9:PC 71 BM is used as the photoactive layer, and e-PH1000 is used as the hole transport layer and the top electrode. The specific preparation method is as follows:
[0059] The cut and patterned transparent electrode indium tin oxide (ITO) glass was ultrasonically cleaned with deionized water (detergent), acetone and isopropanol for 15 minutes. The PEI-Zn electron transport layer was spin-coated on the cleaned ITO glass at 3500 rpm and then heated at 200°C for 20 minutes; PM6:BTP-eC9:PC was spin-coated on the above substrate. 71 BM active layer solution (total concentration of 18.7 mg / mL, mass ratio of 1:1:0.2, solvent is chloroform), the rotation speed is 1500 rpm, and then annealed at 100℃ for 10mins; when the e-PH1000 solution is applied by scraping, the substrate temperature is 70℃, the scraper height is 150μm, and the scraping speed is 15mm / s. The conductivity of the film prepared by e-PH1000 is 5.3×10 2 S / cm, and its work function is 5.4eV.
[0060] The current density-voltage of the organic solar cell device prepared by the method of this example is as follows: Figure 4 In (b), voltage represents voltage, current density represents current density, and a small area (0.04 cm 2 )Device open circuit voltage V OC =0.81V, current density J SC =23.31mA / cm 2 , filling factor FF=0.74, efficiency PCE=14.02%.
[0061] Example 6
[0062] The film prepared by the solvent exchange strategy of the present invention using the alcohol phase conductive polymer formula is directly used as the hole transport layer of the inverse organic solar cell.
[0063] (1) The process of preparing alcohol-phase conductive polymer by the solvent exchange strategy described in the present invention: 6 mL of aqueous PEDOT:PSS (AI 4083) with a mass ratio of 1:6 is loaded into a cellulose lipid semipermeable membrane with a molecular weight cutoff of 500 Da, and the membrane is immersed in 500 mL of isopropanol. The polarities of isopropanol and water are 0.546 and 1.000, respectively. The aqueous solution with high polarity will preferentially penetrate through the semipermeable membrane into the isopropanol solution. After 25 minutes of penetration, more than 93% of the water molecules penetrate into the isopropanol from the dialysis bag, and then 6 mL of isopropanol is added to the PEDOT:PSS. The cells are crushed for 2 hours to completely disperse them in the isopropanol solution, and then the isopropanol-phase polymer PEDOT:PSS solution (e-4083) is obtained.
[0064] (2) Solvent exchange strategy to prepare alcohol phase conductive polymer formula: The prepared e-4083 solution was dynamically spin-coated on clean glass at a spin-coating speed of 3000 rpm. After spin-coating, it was annealed at 100°C for 2 minutes to wait for the alcohol solvent to evaporate. The obtained film thickness was 40nm. Its work function test was 5.0eV and its conductivity test was 4.0×10 -3 S / cm.
[0065] (3) Preparation of inverse organic solar cells: The device structure of inverse organic solar cells is as follows Figure 5 As shown in (a), it is glass / ITO / PEI-Zn / PM6:Y6 / e-4083 / Ag. Among them, ITO glass is the cathode layer, PEI-Zn is the electron transport layer, PM6:Y6 is the photoactive layer, e-4083 is the hole transport layer, and Ag is the anode layer. The specific preparation method is as follows:
[0066] The cut transparent electrode indium tin oxide (ITO) glass was ultrasonically cleaned with deionized water (detergent), acetone and isopropanol for 15 minutes. The PEI-Zn electron transport layer solution was spin-coated on the cleaned ITO glass sheet at 3500 rpm, and then annealed at 150°C for 15 minutes. The PM6:Y6 solution (total concentration of 17.8 mg / ml, mass ratio of 1:1.2, solvent chloroform) was spin-coated on the above substrate at a speed of 2500 rpm and annealed at 100°C for 10 minutes; e-4083 was spin-coated on the above active layer at 3000 rpm; finally, the device was moved to the evaporation chamber and heated at a vacuum pressure of 2.6×10 -7 A 70nm thick silver electrode was deposited at 200 Torr.
[0067] The current density-voltage of the organic solar cell prepared by the method of this example is as follows: Figure 5 In (b), voltage represents voltage, current density represents current density, and open circuit voltage VOC =0.82V, current density J SC =25.86mA / cm 2 , filling factor FF=0.72, efficiency PCE=15.27%.
[0068] Example 7
[0069] The solvent exchange strategy of the present invention is used to prepare the film of the alcohol phase conductive polymer and the antistatic coating is prepared by the blade coating process. The method is as follows:
[0070] (1) The process of preparing alcohol-phase conductive polymer by solvent exchange strategy described in the present invention: Example 4 was repeated with the same steps as described. The conductivity of the film prepared by synthesizing e-4083 was 4.0×10 -3 S / cm.
[0071] (2) Specific preparation process of antistatic coating: 2.5×7.5cm 2 The glass was ultrasonically cleaned with deionized water (detergent), acetone and isopropanol for 15 femins. The clean glass was placed on a scraping table with a substrate temperature of 50°C, 50 μL of alcohol-phase conductive polymer was taken, the slit height was set to 100 μm, the scraping speed was 15 mm / s, and the scraping was performed alternately 1 to 30 times in the forward and reverse directions under the scraping conditions. The film thickness of the film obtained by scraping was adjustable between 20-10,000 nm, and the square resistance was 10 7 -10 10 Adjustable between Ω.
[0072] Example 8
[0073] The solvent exchange strategy of the present invention is used to prepare the film of the alcohol phase conductive polymer formula and the thermoelectric device is prepared by spin coating, and the method is as follows:
[0074] (1) Synthesis of alcohol-phase conductive polymer PEDOT:PSS solution: Example 1 was repeated with the same steps as described above. The conductivity of the film prepared from the synthesized e-PH1000 solution was 6.3×10 2 S / cm.
[0075] (2) Specific preparation process of thermoelectric device: 2.5×5cm 2 The glass was ultrasonically cleaned with deionized water (detergent), acetone and isopropanol for 15 minutes. The e-PH1000 solution was spin-coated on the cleaned glass at a speed of 800 rpm. After the spin coating was completed, it was heated on a hot plate at 100°C for 10 minutes. The film was coated on both ends with an area of 2.5×0.2cm 2 The silver paste is used as the electrode lead.
[0076] The temperature difference-voltage curve of the thermoelectric device prepared by the method of this example is as follows: Figure 6 The Seebeck coefficient obtained by fitting the curve is 28.63μV / K.
[0077] Example 9
[0078] A comparative example of the method for preparing alcohol-phase conductive polymer by solvent exchange described in the present invention is to place 6 mL of aqueous PEDOT:PSS (PH1000) with a mass ratio of 1:2.5 in an ultrafiltration container, extract the solvent therein with a vacuum pump at 5 bar, seal the sealed ultrafiltration container with a semipermeable membrane with a molecular weight of 10,000 Da, remove the solvent therein by using the pressure difference on both sides of the membrane, and add 6 mL of ethanol thereto to prepare a PEDOT:PSS ethanol dispersion. PEDOT has significantly larger aggregation, and it is difficult to eliminate larger solid particles in the ethanol solution even after being treated with an ultrasonic cell crusher for 2 hours. Subsequently, ethylene glycol (EG) is added to increase the conductivity, and the obtained solution is used to prepare an organic solar cell with a trans structure: the device structure of the trans organic solar cell is glass / ITO / PEI-Zn / PM6:BTP-eC9:PC 71 BM / PEDOT:PSS. Among them, ITO glass is the bottom electrode, PEI-Zn is the electron transport layer, PM6:BTP-eC9:PC 71 BM is used as the photoactive layer, and PEDOT:PSS is used as the hole transport layer and the top electrode. The specific preparation method is as follows:
[0079] The cut and patterned transparent electrode indium tin oxide (ITO) glass was ultrasonically cleaned with deionized water (detergent), acetone and isopropanol for 15 minutes. The PEI-Zn electron transport layer was spin-coated on the cleaned ITO glass at 3500 rpm and then heated at 200°C for 20 minutes; PM6:BTP-eC9:PC was spin-coated on the above substrate. 71 BM active layer solution (total concentration of 18.7 mg / mL, mass ratio of 1:1:0.2, solvent is chloroform), the rotation speed is 1500 rpm, and then annealed at 100℃ for 10mins. When scraping PEDOT:PSS alcohol dispersion, the substrate temperature of scraping is 90℃, the scraper height is 150μm, and the scraping speed is 15mm / s. The conductivity of the prepared film is 6.2×10 2 S / cm, and its work function is 4.9eV.
[0080] The voltage of the organic solar cell device prepared by the method of this example represents the voltage, the current density represents the current density, and the small area (0.04cm 2 )Device open circuit voltage V OC =0.65V, current density J SC =21.15mA / cm2 , filling factor FF = 0.54, efficiency PCE = 7.42%. The PEDOT:PSS ethanol dispersion obtained by this ultrafiltration method is applied to the anode of organic solar cells, and the performance is poor. The main reason is that the dispersion concentration of the anionic PSS in the alcohol is low (less than 5 mg / mL), so when the alcohol solvent is directly added to the PEDOT:PSS water solvent while removing it, it is easy to produce large aggregation. Although the same ultrasonic cell pulverization treatment solution as in Example 3 is used, it is still difficult to obtain a uniform and non-aggregated PEDOT:PSS alcohol dispersion, so it is not suitable as an electrode for organic solar cells. In addition, this process relies on ultrafiltration and vacuum equipment, which is not conducive to lightweight production.
[0081] In general, the method for preparing alcohol-phase conductive polymer by solvent exchange provided by the present invention is not only simple in process and easy to process, and the prepared alcohol-phase conductive polymer solution is compatible with various processing surfaces and processing techniques, but also has good application prospects in devices such as organic solar cells, antistatic coatings, and thermoelectric devices.
[0082] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an alcohol-phase conductive polymer by solvent exchange, characterized in that: The following steps are involved: (1) placing an aqueous solution of polyethylene dioxythiophene and anionic polystyrene sulfonic acid into a semipermeable membrane bag, and immersing the semipermeable membrane bag in a first alcohol solvent; due to the difference in polarity between the aqueous solvent and the first alcohol solvent, the aqueous solvent seeps out of the semipermeable membrane bag, while the first alcohol solvent permeates into the semipermeable membrane bag, thereby achieving solvent exchange; (2) adding a second alcohol solvent to the semipermeable membrane bag, and then adding ethylene glycol as a secondary dopant, and then using strong ultrasound to generate a cavitation effect in the liquid, and using an ultrasonic cell crusher to completely disperse the solid particles in the liquid; then adding other types of anionic high-fluorinated sulfonic acid ion polymers not present in the semipermeable membrane bag, stirring and doping, and obtaining the alcohol phase conductive polymer.
2. The method for preparing alcohol-phase conductive polymer by solvent exchange according to claim 1, characterized in that: In the aqueous solution, the molar ratio of polyethylene dioxythiophene to anionic polystyrene sulfonic acid is 1:(2.5-30).
3. The method for preparing alcohol-phase conductive polymer by solvent exchange according to claim 1, characterized in that: The first alcohol solvent described in step (1) and the second alcohol solvent described in step (2) are independently selected from C1-C10 aliphatic alcohols, alicyclic alcohols or aromatic alcohols.
4. An alcohol-phase conductive polymer prepared by the method according to any one of claims 1 to 3.
5. Use of the alcohol-phase conductive polymer as claimed in claim 4 for preparing a thin film.
6. The film obtained by the use as claimed in claim 5.
7. The film obtained by the application as claimed in claim 6, characterized in that: The conductivity of the film is 10 -4 -10 3 S cm -1 , the work function is 4.1-5.4eV.
8. Use of the film according to claim 6 or 7, characterized in that: Specifically, the invention can be used in solar cell electrodes, solar cell hole transport layers, antistatic films, thermoelectric devices or light-emitting diodes.
Citation Information
Patent Citations
Alcohol dispersion liquid of conductive polyethylene dioxythiophene as well as preparation method and application of alcohol dispersion liquid
CN114316223A
Preparation method of organic solvent dispersion liquid of water-based polymer
CN111393678A
Novel polythiophene dispersions
US20020173579A1